Sintesis dan Karakterisasi Abu Kulit Alpukat sebagai Katalis Proses Transesterifikasi Minyak Goreng Bekas menjadi Biodiesel - Azif Afandi; Lindia Riani; Yanna Syamsuddin; Zuhra Zuhra (Fakultas Teknik, 2022)
Biodiesel is synthesized through a transesterification reaction with the help of a catalyst and generally uses a homogeneous catalyst. Heterogeneous catalysts can be synthesized from waste biomass such as avocado peel through a calcination. The purpose of this study was to examine the effect of variations in calcination temperature (550, 650, and 750oC) on the performance of the catalyst for biodiesel production and to analyze the effect of differences in the amount of catalyst (4, 6, 8, and 10% by weight of oil) used in the transesterification process on biodiesel yield. The catalysts were characterized by XRD, SEM-EDX, and FTIR. The results of the characterization of the catalyst showed that the dominant active phase of the catalyst was potassium (K). The highest biodiesel yield was obtained when using avocado peel ash as a catalyst which was calcined at a temperature of 650oC and using 6% catalyst by weight of oil. In the transesterification reaction the composition of the biodiesel product was analyzed using GC-MS and resulted that the palmitic acid was the most abundant composition in biodiesel. The biodiesel products produced were characterized for its density, viscosity, and acid number and have met the standard of SNI 7182:2015.